Impact of Cellphone-Based Tele-Education “Germas Jantungku” On Quality of Life of Patients with Heart Failure Reduced Ejection Fraction in Makassar, Indonesia: A Quasi-randomised Trial - Idar Mappangara; Jaka Eka Yuianto; Akhtar F Muzakkir; Peter Kabo; Pendrik Tandean; Robertus Setiadji; Andriany Qanitha (Physical Activity, Nutrition and Health Sciences Journal, 2025)
Improving quality of life remains a central goal in the management of heart failure (HF). This pilot study aimed to evaluate the effectiveness of tele-education delivered through the Germas Jantungku mobile application, a telemedicine initiative launched in Makassar, Indonesia. A quasi-randomised trial was conducted between May and October 2020 at Wahidin Sudirohusodo Hospital, Makassar. A total of 106 patients with heart failure with reduced ejection fraction (HFrEF) were enrolled. Of these, 53 participants installed the Germas Jantungku application and received tele-education, while 53 participants served as the control group. The primary outcome was quality of life, assessed using the HeartQoL questionnaire one month after the intervention. Participants in the tele-education group demonstrated significantly higher HeartQoL scores compared with the control group (2.31 vs. 1.94, p = 0.01). Within the tele-education group, the mean increase in HeartQoL score from baseline to one month was greater among patients aged <60 years than those aged ≥60 years (0.98 vs. 0.42), females than males (0.85 vs. 0.75), patients with higher education levels than those with mid-to-low education (0.96 vs. 0.66), and NYHA class III–IV than class I–II (0.90 vs. 0.31). A one-month tele-education intervention using the Germas Jantungku mobile application significantly improved HeartQoL scores among patients with HFrEF, with the greatest benefits observed in younger, female, higher-educated patients and those with advanced functional class (NYHA III–IV).